Mechanisms and therapeutics of insulin signaling transduction genes in diabetic cardiomyopathy: a comprehensive updated review - He, Yufeng; Yang, Xi; He, Xinghui; Wang, Guoshuang; Li, Chuang; Yuan, Ping; Li, Chunhong (Frontiers in Endocrinology, 2025)
Diabetic cardiomyopathy (DCM), a complication of type 2 diabetes mellitus (T2DM), is closely associated with key genes in the insulin signaling pathway. Insulin regulates cellular metabolism and growth under normal conditions by activating downstream signaling pathways through its receptors. Nonetheless, insulin resistance, which compromises the insulin signaling pathway and impairs cardiovascular system performance, is common in individuals with T2DM. The key insulin signaling genes include IRS1, IRS2, PIK3R1, and GLUT4 play important roles in insulin receptor signaling, PI3K complex assembly, and glucose transport, respectively. Mutations or abnormal expression of these genes may lead to disorders in the insulin signaling pathway, affecting the normal regulation of glucose metabolism and impairment of myocardial function, thereby promoting the development of DCM. This review delves into the specific roles of these genes in the pathogenic mechanisms and treatment of DCM, with the aim of providing scientific evidence and guidance for future research endeavors.